(untitled) (Research, Society and Development, 2022)
Objective: To analyze the knowledge of nursing professionals about pain during the vaccination of children. Methodology: Descriptive study with a qualitative approach, carried out from January 2017 to January 2018, with 10 nursing professionals from three Basic Health Units in the Federal District, Brazil. Data were collected through interviews using a questionnaire and processed using the IRaMuteQ software. The research was approved by the Research Ethics Committee and all participants signed the Free and Informed Consent Term and the Consent Term for the Use of Image and Sound. Results: The professionals surveyed recognize that children feel pain during vaccination, and they assess it through crying and physiognomy. Regarding the use of non-pharmacological measures, respondents reported not using any action, but they believe that conversation, reception, guidance, mother’s lap and breastfeeding can minimize it. There was also recognition of the importance of treating pain to minimize trauma, anxiety and fear. Final considerations: Professionals have the knowledge about recognizing pain and how to alleviate it, although incipient, however, this knowledge is not transposed into practice; thus, studies are suggested that aim to implement educational practices with professionals involved in the vaccination of children.